Una aproximación a la corrupción política virreinal. La confusión entre lo público y lo privado en el Perú de Felipe V - Moreno Cebrián, Alfredo (2005)
This article analyses the level of enrichment achieved by viceroys Castelldosrius and Castelfuerte. This is a central theme for evaluating the Spanish state, the ways in which the networks of political clientelism were woven during the reign of Philip V, and how all this was projected into the Peruvian viceroyalty. This study is based on a wealth of documentary material and offers a new reading on the political culture of the eighteenth century.